457 - Status of the Resolutions of the Thirteenth Regular Meeting of the IABA and the Twenty-fifth Regular Meeting of the Executive Committee - Executive Committee (EC) (2017)
(DT-489) Avances en el Cumplimiento de las Resoluciones de la XIII Reunión Ordinaria de la JIA-Rev1